SAT0113 Pulmonary Involvement in Rheumatoid Arthritis: is There A Role for Low-Complexity Medical Tests?. (10th June 2014) - Kawassaki, A.M.; Pereira, D.A.S.; Kay, F.U.; Laurindo, I.M.M.; Carvalho, C.R.R.; Kairalla, R.A.
Abstract : Background: Depending on the method of screening, approximately 50% of rheumatoid arthritis (RA) patients may exhibit lung involvement, but most cases are subclinical. Objectives: To evaluate whether simple methods can yield relevant disease information from RA patients. Methods: RA patients from a Brazilian single terciary center were randomly selected for a cross-sectional clinical pulmonary evaluation, rest pulse oximetry, chest X-ray (CXR) and spirometry. Based on a prevalence assumption for abnormal spirometry of 30%, the sample size estimated for 1, 000 patients at regular follow-up was 245, with 5% precision. The study was approved by local research ethics committee. Written informed consent was obtained from all participants. Results: A total of 246 RA patients underwent complete assessments. Half of the population reported tobacco exposure. Spirometry was abnormal in 30% of the patients; CXR was abnormal in 45%, and pulse oximetry was abnormal in 13%. Normal CXR, spirometry and oximetry were observed simultaneously in only 41% of the RA patients. Tobacco exposure was associated with abnormal (p=0.006), obstructive (p=0.02) and restrictive (p=0.045) spirometry, and with abnormal (p=0.0005) and interstitial-patterned CXR (p=0.01). After adjusting for confounders, abnormal medical were associated with male gender (p=0.025), older age (p=0.004), positive rheumatoid factor (p=0.0003), disease duration (p=0.016) and smoking (p<0.0001). Notably, signs of airway disease were observed in nearly half of the patients with low or absent tobacco exposure. Conclusions: A combination of simple, non-hazardous, inexpensive pulmonary evaluation methods can diagnose pulmonary disease in RA patients. Our results lead us to suggest that asymptomatic patients with mild lung involvement should undergo regular pulmonary evaluations, with further investigation if new symptoms develop or in the case of disease progression. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6050